Acute phase response and inflammation following pulmonary exposure to low doses of zinc oxide nanoparticles in mice. Issue 9 (21st October 2019) - Hadrup, Niels; Rahmani, Feriel; Jacobsen, Nicklas R.; Saber, Anne T.; Jackson, Petra; Bengtson, Stefan; Williams, Andrew; Wallin, Håkan; Halappanavar, Sabina; Vogel, Ulla
Abstract: Inhalation of nanosized zinc oxide (ZnO) induces metal fume fever and systemic acute phase response in humans. Acute phase response activation is a cardiovascular risk factor; we investigated whether pulmonary exposure of mice can be used to assess ZnO-induced acute phase response as well as inflammation and genotoxicity. Uncoated (NM-110) and triethoxycaprylylsilane-coated (NM-111) ZnO nanoparticles were intratracheally instilled once at 0.2, 0.7 or 2 µg/mouse (11, 33 and 100 µg/kg body weight). Serum amyloid A3 mRNA level in lung tissue, bronchoalveolar lavage (BAL) fluid cellularity, and levels of DNA strand breaks in BAL fluid cells, lung and liver tissue were assessed 1, 3 and 28 days post-exposure. Global transcription patterns were assessed in lung tissue using microarrays. The acute-phase response serum amyloid A3 mRNA levels were increased on day 1; for uncoated ZnO nanoparticles at the highest dose and for coated ZnO nanoparticles at medium and highest dose. Neutrophils were increased in BAL fluid only after exposure to coated ZnO nanoparticles. Genotoxicity was observed only in single dose groups, with no dose-response relationship. Most changes in global transcriptional response were observed after exposure to uncoated ZnO nanoparticles and involved cell cycle G2 to M phase DNA damage checkpoint regulation. Although, uncoated and coated ZnO nanoparticles qualitatively exerted similar effects, observed differences are likely explained by differences in solubility kinetics. The finding of serum amyloid A3 induction at low exposure suggests that mouse models can be used to assess the nanoparticle-mediated induction of acute phase responses in humans.